Triboelectric nanogenerator enhanced radical generation in a photoelectric catalysis system via pulsed direct-current. (September 2022) - Dong, Feilong; Pang, Zhen; Lin, Qiufeng; Wang, Da; Ma, Xiaoyan; Song, Shuang; Nie, Shuangxi
Abstract: Traditional photoelectric catalysis technologies are limited by the needs for large external energy input. In this study, the self-powered photoelectric catalysis was established by a spherical triboelectric nanogenerator (S-TENG) under a pulsed direct-current electric field to improve the removal rate of Atrazine (ATZ). Also, the electrical output performance of S-TENG was tested. To further improve the utilization of light and degradation efficiency of ATZ, the photoelectrode (TiO2 nanotube) and photocatalyst (6HF-TiO2 nanosheets) were both used to degrade ATZ. The removal rate of ATZ was enhanced by 8.53%, and the mineralization was increased by 27.2% within 30 min in the photoelectric catalysis system with pulse direct-current electric field by S-TENG. The degradation mechanism of ATZ was also demonstrated by the EPR tests and free radicals quenching experiments. The result showed that the photogenerated free radicals were increased by triboelectric pulsed direct-current during the photoelectric catalysis degradation. The hydroxyl radical (OH) played an essential role in the degradation of ATZ in the self-powered photoelectric catalysis system. In addition, the degradation pathway of ATZ was proposed in detail based on LC-MS/MS test and density functional theory (DFT) calculation. Furthermore, the toxicity of ATZ and its degradation intermediates were evaluated by the ECOSAR program. Overall, this research provides a novel strategy for enhancing the performance of self-powered photoelectric catalysis processes for wastewater treatment. Graphical Abstract: ga1 Highlights: S-TENG was designed for harvesting water wave energy in wastewater treatment. The pulse direct-current electric field by S-TENG was used for photoelectric catalysis. ATZ removal was enhanced with pulse direct-current electric field by S-TENG. The photogenerated radicals were increased by triboelectric pulsed direct-current. The degradation pathway and toxicity of ATZ was proposed in detail.